Elements of traditional Tuvan cosmology in the state emblem of the People’s Republic of Tuva, 1935-1939 - Mongush, Boris B. (The New Research of Tuva, 2016)
The article examines the constituent elements of the state emblem of the People’s Republic of Tuva (in its 1935/1939 version). We view state emblems as a special type of historical source where constituent emblems and elements are, in fact, reflections of a certain worldview. Emblems of the People’s Republic of Tuva (PRT) originally were full of Buddhist religious symbolism, but in the course of time it switched over to representing the dominance of the Soviet heraldic symbolism. Among the variety of the PRT’s emblems created between 1921 and 1941, a special place belongs to the 1935 version. In 1939 it was slightly modified, but the basics of the design were left unchanged for several more years. This was a highly original state emblem which had nothing in common with those of USSR, Mongolia, or any of the subsequent emblems of Tuva. The official blazon of the state emblem can be found in the report of the Chairman of the Presidium of the PRT’s Little Khural to the Great Khural on amendments to the Constitution and on the new Constitution of Tuva (1936). The azure five-petal flower-like escutcheon was traditionally interpreted as an influence of Soviet heraldry – “a blunt-pointed star” – thus imagined as a reflection of the Socialist policy of PRT’s government. A comparative analysis, however, shows that the five-petal design corresponds to the circle of a classical mandala (the sky or space), while the outlines of the PRT matches the central square if the mandala. A rider placed within the outline in this context represents the master of this space. The tinctures fit into this interpretation well: the outline of the PRT is greyish-brown (for earth). All in all, the symbolism of the emblem is a harmonized formula of the world as seen by Tuvans: Space ↔ Earth ↔ masters of the land. We believe that the similarities between the mandala and the PRT’s 1935/1939 state emblem are far from a mere coincidence. They prove that old Turkic cultural tradition had been deeply integrated into the Buddhist one and left a deep imprint on Tuvan mentality. Despite the impact of Soviet heraldry on the appearance and interpretation of the state emblem of Tuva, in its basics the emblem remained within the Turko-Mongolian, specifically Tuvan, symbolism.